DOP68 Autophagy induction in the intestinal epithelium protects against inflammation-induced barrier loss in vivo. (30th January 2023) - Saha, K; Ganapathy, A S; Wang, A; Morris, N; Yochum, G; Koltun, W; Ding, W; Nighot, M; Ma, T; Nighot, P
Abstract: Background: Loss of the paracellular tight junction (TJ) barrier and defective autophagy in the gut are pathogenic factors for inflammatory bowel disease (IBD). Earlier, we demonstrated the role of autophagy in the degradation of the pore-forming claudin-2 protein and the resultant TJ barrier enhancement. Here, we investigated the role of autophagy in the regulation of the TJ barrier in vivo and in Crohn's disease (CD) patient-derived tissues and patient-derived organoids. Methods: Wild type and autophagy-deficient Atg7 -/- mice were given intraperitoneal rapamycin injection to induce autophagy along with LPS or TNF-α to induce inflammation. Surgically resected tissues from CD patients were incubated with rapamycin and the paracellular barrier was measured by Ussing chambers. Autophagy was induced in human colonic organoids by incubation with either rapamycin or by nutrient starvation. Results: Intraperitoneal rapamycin injection in WT mice successfully induced autophagy as evidenced through the degradation of the autophagy substrate p62/SQSTM. Rapamycin injection increased the colonic occludin levels and enhanced the paracellular TJ barrier as evidenced by the decreasing paracellular flux of inulin. Rapamycin prevented LPS and TNF-a induced colonic paracellular barrier loss and reduction in occludin levels in WT mice. Rapamycin reduced the LPS and TNF-a-induced increase in occludin's association with caveolin-1 thereby preventing its caveolae-mediated endocytosis and degradation. The protective effect of rapamycin was dependent on autophagy. Conditional knockout of Atg7 (cAtg7) in mouse colon decreased baseline occludin levels and increased inulin flux in mouse colon. Furthermore, rapamycin failed to prevent the LPS and TNF-a-induced colonic barrier loss in the cAtg7 mice. Additionally, these mice lacking the ability to undergo autophagy in the colon were more susceptible to Dextran Sodium Sulphate (DSS)-induced colitis. In normal and inflamed colonic tissues from CD patients, incubation with rapamycin induced autophagy, evidenced through the reduction in p62/SQSTM1 protein levels, increased occludin levels and enhanced the paracellular TJ barrier. Autophagy induction by rapamycin or nutrient starvation also increased occludin levels and its membrane localization in patient-derived organoids. Conclusion: Our data show that rapamycin successfully induced autophagy in WT mice's colon and protected these mice from the barrier disruptive effect of both LPS and TNF-α, indicating the importance of autophagy in regulating the intestinal TJ barrier. Our data also highlights the application of autophagy induction as a potential therapeutic approach in the treatment of IBD.